Intracranial hypertension secondary to low doses of vitamin A - Dach , Fabíola; Haes , Tissiana (Headache Medicine, 2022)
Introduction Chronic Vitamin A toxicity usually occurs with high doses of Vitamin A intake, usually after using >30,000mcg EA daily for several months. For treatment of skin disorders isused massive doses (50,000 to 150,000 mcg AE daily). Early signs and symptoms can be sparsely distributed rough hair, alopecia of the eyebrows, rough and dry skin, dry eyes and chapped lips. Later, severe headache, intracranial hypertension, and generalized weakness develop. Fractures can easily occur, especially in the elderly. Objective To present a case of intracranial hypertension secondary to chronic intake of low doses of Vitamin A. Method Revision of medical record. Case Woman, 60 years old, thin, presents with worsening headaches for two years. Since childhood, she has had migraine without aura in low-frequency. In the last two years, she has had some changes in headache characteristics, however she still met criteria for migraine. Pain occurred daily and there were four episodes of nocturnal awakenings by pain in the last year. Magnetic resonance imaging of the brain and venous-phase magnetic resonance angiography normal. A cerebrospinal fluid analysis was requested, which showed an opening pressure of 92cmH2O and a closing pressure of 40cmH2O. No futher abnormalities. Acetazolamide 250mg twice a day was started, with intolerance and metabolic acidosis after 3 days of use. It was replaced by topiramate, to which there was also intolerance at a dose of 25mg twice a day for 7 days of use. Asked again by the use of any medine/vitamin, patient revealed that use two capsules of propolis for fourteen years, whose leaflet showed the presence of 300 mcg EA of vitamin A in each capsule of the compound. Patient was advised to discontinue its use and to repeat cerebrospinal fluid analysis in three months, whose opening... (To see the complet abstract, please, check out the PDF.)